PENGARUH KOMUNIKASI ORGANISASI DAN PENILAIAN PRESTASI KERJA TERHADAP KINERJA KARYAWAN (STUDI BAGIAN KANTOR PT. ASRINDO CITRASENI SATRIA DURI) - Nur Syakinah; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The company is one of the large and comprehensive forms of organization contained in it human beings who act as mobilizers to advance the company. This research uses this type of research with quantitative approach. As for the independent variables of this research, Organizational Communication (X1) and Work Achievement Assessment (X2). As for dependent variables in this research Employee Performance (Y). Sampling techniques using Proportionate Stratified Random Sampling method, then data collection techniques through questionnaires and interviews to employees of PT office. Asrindo Citraseni Satria Duri. Data processing uses simple linear regression analysis and multiple linear regression using SPSS 25.This study aims to determine the influence of organizational communication and assessment of work performance on employee performance. The sample of this study was taken by 57 respondents. The results of this study showed that organizational communication affects employee performance. Work performance assessment affects employee performance. Organizational communication and work achievement assessment affect employee performance. Keywords: Organizational Communication, Work Achievement Assessment, Employee Performance, PT. Asrindo Citraseni Satria Duri